Pelatihan Pemanfaatan Limbah Cangkang Kerang Dengan Metode 3P (Pembersihan, Pembuatan, dan Penjualan) di Desa Banjar Kemuning - Lestari; M. Mustaqim; Muttaqin, Ridwan Maf'ul; Wicaksono, Arif; Widiana, Ilvi Nur; Asnifa, Siti; Noviyanti, Masyitah (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
This article describes the potential and utilization of clam shell waste with 3P training (Cleaning, Making, and Selling) as an alternative to making various decorative handicrafts. Clam shell waste, which is generally ignored, has the potential to be utilized as raw material in various industries. This article focuses on practical steps in integrating the 3P concept in the management of this waste. In addition to reducing shell waste, kerrang shells can also improve the economy as they have aesthetic value and economic value. In the Cleaning stage, efforts are made to clean and sort the shells from other materials. This step is important to ensure the quality of the raw materials produced. Next, at the manufacturing stage, the shells enter the assembly process to produce craft products. The last stage is selling the shell products online and in e-commerce. The target of this training activity is PKK women in Banjar Kemuning village.